Objective methods for determining criteria weight coefficients: A modification of the CRITIC method - Žižović, Mališa; Miljković, Boža; Marinković, Dragan (Decision Making: Applications in Management and Engineering, 2020)
Determining criteria weight coefficients is a crucial step in multi-criteria decision making models. Therefore, this problem is given great attention in literature. This paper presents a new approach in modifying the CRiteria Importance Through Intercreteria Correlation (CRITIC) method, which falls under objective methods for determining criteria weight coefficients. Modifying the CRITIC method (CRITIC-M) entails changing the element normalization process of the initial decision matrix and changing data aggregation from the normalized decision matrix. By introducing a new normalization process, we achieve smaller deviations between normalized elements, which in turn causes lower values of standard deviation. Thus, the relationships between data in the initial decision matrix are presented in a more objective way. By introducing a new process of aggregation of weight coefficient values in the CRITIC-M method, a more comprehensive understanding of data in the initial decision matrix is made possible, leading to more objective values of weight coefficients. The presented CRITIC-M method has been tested in two examples, followed by a discussion of results via comparison to the classic CRITIC method.